INTERDEPENDENSI STRATEGI PEMASARAN PERUSAHAN TERHADAP KINERJA PERUSAHAAN ASURANSI DI INDONESIA - Hidayat, Cecep (Jurnal Manajemen Update, 2012)
This study aims to analyze the interdependence between the variables of marketing strategy and organizational performance of insurance companies using canonical correlation analysis multiple multivariate analysis approach. Correlation value is interdependence will be able to explain the subgroup where the dominant variable affecting other subgroups on the company based on the value of redundancy index. The study population was 9 insurance companies that go public when the study was conducted in 2013. Given two exogenous variables, i.e. variables Effectiveness Strategy (STRAEFEK) and Efficiency Strategy (STRATEFIS). Endogenous variable is the Debt to Asset Ratio (DAR), Debt to Eqiity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Operating Profit Margin (OPM) and Net Profit Margin (NPM). Keyword: interdependence, Strategy Effectiveness, Efficiency Strategy